2018
DOI: 10.2147/copd.s156617
|View full text |Cite
|
Sign up to set email alerts
|

Harmful impact of air pollution on severe acute exacerbation of chronic obstructive pulmonary disease: particulate matter is hazardous

Abstract: IntroductionParticulate matter and air pollution in Korea are becoming worse. There is a lack of research regarding the impact of particulate matter on patients with COPD. Therefore, the purpose of this study was to investigate the effects of various air pollution factors, including particulate matter, on the incidence rate of severe acute exacerbations of COPD (AECOPD) events.MethodsWe analyzed the relationship between air pollutants and AECOPD events that required hospitalization at Guro Hospital in Korea fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 46 publications
1
53
0
1
Order By: Relevance
“…Most probably the hospitalized patients were more vulnerable to the detrimental effect of air pollutants than community dwellers as they were more seriously ill and remained exposed to the ambient air (e.g., housing style, occupation, protection awareness) might also be explained by the differences in disease severity and management (30). Emergency visits for AECOPD increased shortly (lag 1 day) after increased level of PM 2.5 (8,10) while, the association between hospital admissions for AECOPD was positive for both PM 10 and PM 2.5 on lag day3 as shown in previous studies (4,6,11,31,32).…”
Section: Discussionmentioning
confidence: 56%
“…Most probably the hospitalized patients were more vulnerable to the detrimental effect of air pollutants than community dwellers as they were more seriously ill and remained exposed to the ambient air (e.g., housing style, occupation, protection awareness) might also be explained by the differences in disease severity and management (30). Emergency visits for AECOPD increased shortly (lag 1 day) after increased level of PM 2.5 (8,10) while, the association between hospital admissions for AECOPD was positive for both PM 10 and PM 2.5 on lag day3 as shown in previous studies (4,6,11,31,32).…”
Section: Discussionmentioning
confidence: 56%
“…6 A meta-analyses suggest that PM exposure can increase COPD exacerbations, 2 7-9 and a recent study showed that PM and other air pollutants increased the risk of severe acute exacerbations. 10 Air pollutants can also Strength and limitations of this study ► This is the first prospective panel study conducted in Korea to assess the relationship between particulate matter (PM) exposure and symptoms, lung function, quality of life and exacerbations in patients with chronic obstructive pulmonary disease (COPD). ► A total of 120 patients from four different sites will be enrolled from three different areas of Korea to represent real-world air quality, accounting for regional differences in PM exposure.…”
Section: Introductionmentioning
confidence: 99%
“…2015) reported the effects on central nervous system in infants and young children due to ozone and PM 10 . Additionally,Choi et al (2018) indicated that PM is hazardous for human health since is considered a major non-infectious cause of severe acute exacerbation of chronic obstructive pulmonary disease (COPD). The comparison of mass concentrations displayed inFigure 5shows that despite the efforts of Mexico City authorities, inhabitants remain exposed to PM 2.5 ; therefore, continuous studies related with monitoring and characterization of PM are necessary.…”
mentioning
confidence: 99%